Regulatory T cells are strong promoters of acute ischemic stroke in mice by inducing dysfunction of the cerebral microvasculature - Kleinschnitz, Christoph; Kraft, Peter; Dreykluft, Angela; Hagedorn, Ina; Göbel, Kerstin; Schuhmann, Michael K.; Langhauser, Friederike; Helluy, Xavier; Schwarz, Tobias; Bittner, Stefan; Mayer, Christian T.; Brede, Marc; et al. (Blood, 2013)
We have recently identified T cells as important mediators of ischemic brain damage, but the contribution of the different T-cell subsets is unclear. Forkhead box P3 (FoxP3)-positive regulatory T cells (Tregs) are generally regarded as prototypic anti-inflammatory cells that maintain immune tolerance and counteract tissue damage in a variety of immune-mediated disorders. In the present study, we examined the role of Tregs after experimental brain ischemia/reperfusion injury. Selective depletion of Tregs in the DEREG mouse model dramatically reduced infarct size and improved neurologic function 24 hours after stroke and this protective effect was preserved at later stages of infarct development. The specificity of this detrimental Treg effect was confirmed by adoptive transfer experiments in wild-type mice and in Rag1−/− mice lacking lymphocytes. Mechanistically, Tregs induced microvascular dysfunction in vivo by increased interaction with the ischemic brain endothelium via the LFA-1/ICAM-1 pathway and platelets and these findings were confirmed in vitro. Ablation of Tregs reduced microvascular thrombus formation and improved cerebral reperfusion on stroke, as revealed by ultra-high-field magnetic resonance imaging at 17.6 Tesla. In contrast, established immunoregulatory characteristics of Tregs had no functional relevance. We define herein a novel and unexpected role of Tregs in a primary nonimmunologic disease state.
Prepublished online as Blood first edition paper, November 15, 2012
Gesehen am 08.06.2022